2007
DOI: 10.1038/nn1980
|View full text |Cite
|
Sign up to set email alerts
|

A complexin fusion clamp regulates spontaneous neurotransmitter release and synaptic growth

Abstract: Neuronal signaling occurs through both action potential-triggered synaptic vesicle fusion and spontaneous release, although the fusion clamp machinery that prevents premature exocytosis of synaptic vesicles in the absence of calcium is unknown. Here we demonstrate that spontaneous release at synapses is regulated by complexin, a SNARE complex-binding protein. Analysis of Drosophila melanogaster complexin null mutants showed a marked increase in spontaneous fusion and a profound overgrowth of synapses, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
359
5
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(380 citation statements)
references
References 15 publications
14
359
5
2
Order By: Relevance
“…S4). Thus, the complexin knock-down greatly impaired fast synchronous but not asynchronous synaptic vesicle fusion, and increased spontaneous fusion, thereby reconciling the divergent phenotypes observed in vertebrate autapses, Drosophila neuromuscular junctions, and in vitro fusion assays [7,[10][11][12][13][14][15].We next examined which complexin sequences mediate spontaneous and evoked fusion (Fig. 1C).…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…S4). Thus, the complexin knock-down greatly impaired fast synchronous but not asynchronous synaptic vesicle fusion, and increased spontaneous fusion, thereby reconciling the divergent phenotypes observed in vertebrate autapses, Drosophila neuromuscular junctions, and in vitro fusion assays [7,[10][11][12][13][14][15].We next examined which complexin sequences mediate spontaneous and evoked fusion (Fig. 1C).…”
mentioning
confidence: 74%
“…Later responses during the train's asynchronous phase were normal, and delayed release was enhanced (Figs. 3H-3J and S13), thus rendering the WA-mutation a weaker phenocopy of the synaptotagmin-1 KO, the complexin KO, the complexin knockdown, and the synaptobrevin 3A-mutation phenotype (7,15,21;. In contrast to the WA-mutation, the 85-and 86-mutations did not impair rescue of synaptic transmission by synaptobrevin in synaptobrevin-deficient neurons (Fig.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Initial in vitro studies using cell-cell fusion or lipid-mixing assays indicated that Cpx prevents in vitro membrane fusion events, suggesting Cpx may act as a fusion clamp to prevent premature exocytosis in the absence of Ca 2+ (11,14,15). Consistent with the role of Cpx in clamping synaptic fusion, in vivo experiments in Drosophila revealed a dramatic increase in spontaneous synaptic vesicle fusion events (minis) in cpx null mutants (16). In addition to enhanced minis, cpx mutants have reduced evoked release.…”
mentioning
confidence: 92%